FREQUENCY AND PREDICTORS OF RADIAL ARTERY SPASM DURING CORONARY ANGIOGRAPHY/PERCUTANEOUS CORONARY INTERVENTION - khan, Matiullah; daud, Muhammad Yousuf; Awan, Muhammad Saleem; Khan, Muhammad Imran; Khan, Hazratullah; Yousuf, Muhammad Awais (Journal of Ayub Medical College Abbottabad, 2020)
Background: Coronary angiography is the gold standard test for diagnosis coronary artery disease. It can be performed via various intra-arterial routes, i.e., femoral, radial, brachial, ulnar, or axillary arteries. Trans-Radial access for coronary angiography is a good approach with less major vascular complications, increased patient comfort and early mobilization and less hospital stay but is associated with radial artery spasm as the major complication effecting the success of the procedure. Methods: This study was a descriptive cross-sectional study. It enrolled one hundred and thirty-six (136) consecutive patients who underwent the procedure of coronary angiography/PCI over a 6-month period. The study included both in and outpatients undergoing coronary angiography/PCI. Coronary angiography/Percutaneous coronary intervention was done via trans radial approach and the study participants were observed for development of radial artery spasm using clinical and angiographic parameters. Data was entered and analysed using SPSS-19. Results: The frequency of radial artery spasm was 13.24% (n=18). Radial artery spasm was statistically significant in females (p<0.05), those who had severe pain during radial artery puncture (p<0.001) and those who had unsuccessful first attempt during radial artery puncture (p<0.001). No statistically significant association was found between radial artery spasm and other predictors such as age, hypertension and diabetes mellitus. Conclusion: Radial artery spasm is a common complication during trans radial approach for coronary angiography/percutaneous coronary intervention particularly in females, those who have unsuccessful first attempt and those who have severe pain during radial artery puncture. Keywords: Coronary angiography; PCI; Radial artery spasm Background: Coronary angiography is the gold standard test for diagnosis coronary artery disease. It can be performed via various intra-arterial routes, i.e., femoral, radial, brachial, ulnar, or axillary arteries. Trans-Radial access for coronary angiography is a good approach with less major vascular complications, increased patient comfort and early mobilization and less hospital stay but is associated with radial artery spasm as the major complication effecting the success of the procedure. Methods: This study was a descriptive cross-sectional study. It enrolled one hundred and thirty-six (136) consecutive patients who underwent the procedure of coronary angiography/PCI over a 6-month period. The study included both in and outpatients undergoing coronary angiography/PCI. Coronary angiography/Percutaneous coronary intervention was done via trans radial approach and the study participants were observed for development of radial artery spasm using clinical and angiographic parameters. Data was entered and analysed using SPSS-19. Results: The frequency of radial artery spasm was 13.24% (n=18). Radial artery spasm was statistically significant in females (p<0.05), those who had severe pain during radial artery puncture (p<0.001) and those who had unsuccessful first attempt during radial artery puncture (p<0.001). No statistically significant association was found between radial artery spasm and other predictors such as age, hypertension and diabetes mellitus. Conclusion: Radial artery spasm is a common complication during trans radial approach for coronary angiography/percutaneous coronary intervention particularly in females, those who have unsuccessful first attempt and those who have severe pain during radial artery puncture. Keywords: Coronary angiography; PCI; Radial artery spasm